Marine epizootics linked to storms: Mechanisms of pathogen introduction and persistence inferred from coupled physical and biological time‐series. (23rd October 2015) - Feehan, Colette J.; Scheibling, Robert E.; Brown, Michael S.; Thompson, Keith R.
Abstract: Along the Atlantic coast of Nova Scotia sea urchin disease outbreaks are statistically linked to North Atlantic hurricanes and warm sea temperatures. The amoebic pathogen Paramoeba invadens, which causes these disease outbreaks, is unable to withstand typical minimum sea temperatures along this coast, suggesting that it is reintroduced during periods of peak temperatures. Here, we examine hypotheses for mechanisms of introduction or persistence of P. invadens using data on sea urchin disease outbreaks from a 5‐yr field experiment (2010–2014), in combination with high‐temporal‐resolution oceanographic and meteorologic data. Disease outbreaks were observed in 4 yr, with the onset of mass mortality (≥50% morbidity or mortality) ranging from mid August to mid October. Physical data suggest that P. invadens originates in warm offshore surface waters that are transported to the coast during strong storms. Disease outbreaks were associated with passing hurricanes in 2 yr (2010 and 2011). In 2012, a disease outbreak occurred in the absence of a storm and following a strong positive anomaly in winter sea temperature, suggesting survival of the pathogen from 2011. In 2014, a disease outbreak occurred in association with a strong storm (nor'easter) that was not a hurricane. Our findings indicate that changing environmental conditions of increasing minimum sea temperatures and increasing intensity of storms may be altering the dynamics of this disease. These inferences remain equivocal, however, indicating the need for high‐resolution dynamical modeling of the physical environment and rapid identification of P. invadens in the environment using genetic tools.